Quantitative sensory testing in dogs with spontaneous osteoarthritis - James Russell Hunt; David Knazovicky; Megan Goff; John Harris; Toby G. Knowles; Masataka Enomoto; Michael Mendl; Becky Whay; B. Duncan X. Lascelles; B. Duncan X. Lascelles; B. Duncan X. Lascelles; B. Duncan X. Lascelles; et al. (Frontiers in Pain Research)
ObjectiveTo investigate changes in somatosensory sensitivity in dogs with spontaneous osteoarthritis (OA) and pain of the stifle or hip, compared to a group of healthy control dogs.Study designA non-randomised, non-blinded, prospective research study.Animals30 control, 51 OA-pain, and 31 OA-pain dogs receiving NSAIDsMethodsA range of noxious and non-noxious quantitative sensory testing (QST) modalities were applied. Dogs were tested twice, one month apart. Two sites were tested at each visit: a distal site located on the cranial aspect of the mid metatarsus and a primary site, lateral to the patella (in dogs with stifle OA) or craniodorsally to the greater trochanter (in dogs with coxofemoral OA). Control dogs were tested at appropriate primary sites to produce the same proportion of animals being tested at stifle or hip as those in the OA group. The order in which non-nociceptive and nociceptive tests were performed was randomized for each test site for each animal, although nociceptive tests were always performed after non-nociceptive tests. Feasibility for performing the tests was assessed for the final 45 dogs recruited to the study. The hierarchical structure of the QST testing data was accounted for within the statistical analysis by employing general linear modelling within a multilevel modelling framework using the MLwiN statistics package.ResultsOsteoarthritis category was not a major determinant of QST outcome measures for the majority of modalities evaluated. In the few modalities in which OA category was determined to be a significant predictor variable, the results were not consistent with previously reported data. The novel, non-nociceptive tests employed overall suggested non-noxious hypoesthesia in association with OA pain. The feasibility of performing QST assessments was relatively low compared to previous studies.Conclusionsand clinical relevance: In a clinical environment, the variability in feasibility of performing QST between dogs may be sufficient to confound changes in QST outcome measures associated with spontaneous OA.